Timeless or tainted? The effects of male ageing on seminal fluid - Fricke, Claudia; Sanghvi, Krish; Emery, Mischa; Lindenbaum, Ina; Wigby, Stuart; Ramm, Steven A.; Sepil, Irem (Frontiers in Ecology and Evolution, 2023)
Reproductive ageing can occur due to the deterioration of both the soma and germline. In males, it has mostly been studied with respect to age-related changes in sperm. However, the somatic component of the ejaculate, seminal fluid, is also essential for maintaining reproductive function. Whilst we know that seminal fluid proteins (SFPs) are required for male reproductive success across diverse taxa, age-related changes in SFP quantity and composition are little understood. Additionally, only few studies have explored the reproductive ageing of the tissues that produce SFPs, and the resulting reproductive outcomes. Here we provide a systematic review of studies addressing how advancing male age affects the production and properties of seminal fluid, in particular SFPs and oxidative stress, highlighting many open questions and generating new hypotheses for further research. We additionally discuss how declines in function of different components of seminal fluid, such as SFPs and antioxidants, could contribute to age-related loss of reproductive ability. Overall, we find evidence that ageing results in increased oxidative stress in seminal fluid and a decrease in the abundance of various SFPs. These results suggest that seminal fluid contributes towards important age-related changes influencing male reproduction. Thus, it is essential to study this mostly ignored component of the ejaculate to understand male reproductive ageing, and its consequences for sexual selection and paternal age effects on offspring.